Layanan Konseling Kelompok Terhadap Self Confidence - Muhammad Syamsul Arifin; Titin Swastinah; Sitti Ernawati (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2019)
This research is the target to be achieved through a series of research activities. Thus, this study specifically aims to determine the Effect of Group Counseling Services on Self Confidence of Class XI Students of HidayatulMubtadiin Vocational School, SidodadiTempurejo, Academic Year 2018/2019.Based on the results of the study, the results of the analysis showed that the value of rxy obtained was 0.458. This number is greater and the r table is significant at 5% = 0.202 with the number of respondents (N) = 95. This result gives the understanding that the null hypothesis (Ho) reads "There is no Effect of Group Counseling Services on Self Confidence of Hidayatul Vocational High School Students MubtadiinSidodadiTempurejo 2018/2019 Academic Year "was rejected. While the working hypothesis (Ha) which reads, "There is the Effect of Group Counseling Services on Self Confidence of Class XI Students of HidayatulMubtadiin Vocational School, SidodadiTempurejo 2018/2019 Academic Year," accepted. Thus the conclusion was the influence of Group Counseling Services on Self Confidence of Class XI Students of HidayatulMubtadiin Vocational School, SidodadiTempurejo, Academic Year 2018/2019. Keywords: Group Counseling, Self Confidence